2022
DOI: 10.3389/fmicb.2022.826827
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Bacillus tequilensis GYUN-300: An Antagonistic Bacterium Against Red Pepper Anthracnose Caused by Colletotrichum acutatum in Korea

Abstract: Anthracnose is a fungal disease caused by Colletotrichum species and has detrimental effects on many crops, including red pepper. This study used Bacillus tequilensis GYUN-300 (GYUN-300), which exhibit antagonistic activity against the fungal pathogen, Colletotrichum acutatum. This pathogen causes anthracnose that manifests primarily as a fruit rot in red pepper. There have been little efforts to identify antagonistic bacteria from mushrooms; this strain of bacteria was identified as B. tequilensis using BIOLO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 79 publications
(89 reference statements)
1
7
1
Order By: Relevance
“…Previous studies found that B. tequilensis can quickly and stably colonize plants, and has a high propagation rate and a strong proliferative capacity [ 30 ]. B. tequilensis has high efficiency and broad-spectrum resistance to plant pathogens, has a combined treatment effect on plant diseases such as anthracnose [ 31 ] and black spot disease [ 32 ], has a high prevention effect, and has good application prospects for the prevention and control of plant diseases [ 33 ]. However, it has never been reported for γ-PGA production; therefore, B. tequilensis BL01 was selected for subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies found that B. tequilensis can quickly and stably colonize plants, and has a high propagation rate and a strong proliferative capacity [ 30 ]. B. tequilensis has high efficiency and broad-spectrum resistance to plant pathogens, has a combined treatment effect on plant diseases such as anthracnose [ 31 ] and black spot disease [ 32 ], has a high prevention effect, and has good application prospects for the prevention and control of plant diseases [ 33 ]. However, it has never been reported for γ-PGA production; therefore, B. tequilensis BL01 was selected for subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Shin et al (2021) demonstrated that the application of the antagonistic bacteria, B. velezensis BS1 at a concentration of 10 5 × CFU/mL significantly ( p < 0.05) reduced the anthracnose disease caused by Colletotrichum scovillei on hot pepper fruits when compared to the untreated control group. Furthermore, Kwon et al (2022) achieved red pepper anthracnose control using Bacillus tequilensis GYUN-300 with only 14% disease incidence under field conditions. In contrast, Kim et al (2023) recently demonstrated disease control of anthracnose caused by C. acutatum in red peppers with a significant ( p < 0.05) reduction of disease rate (0.4%) by pre-immersion with Brevibacillus halotolerans B-4359 when compared to foliar spray and soil drench methods under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A field experiment was carried out to investigate the biological control of hot pepper anthracnose using GYUN-2311 antagonistic bacteria in Korea. Initially, the seedlings were grown in plastic trays (36 pots per tray) with one seed per pot ( Kwon et al, 2022 ). Three-week-old hot pepper (cv.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies found that B. tequilensis can quickly and stably colonize plants, and has a high propagation rate and strong in proliferative capacity (Shultana et al 2021). B. tequilensis has high e ciency and broad-spectrum plant pathogen resistance, has a combined treatment effect on plant diseases such as anthracnose (Kwon et al 2022) and black spot disease (Xu et al 2021), has a high prevention effect, and has good application prospects for the prevention and control of plant diseases (Guerrero-Barajas et al 2020). However, it has never been reported for γ-PGA production; therefore, B. tequilensis BL01 was selected for subsequent experiments.…”
Section: Screening Of Highly γ-Pga-producing Strainsmentioning
confidence: 99%